2016
DOI: 10.3389/fncel.2016.00079
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Activation of Group I Metabotropic Glutamate Receptors Increases Functional TRPV1-Expressing Neurons in Mouse Dorsal Root Ganglia

Abstract: Damaged tissues release glutamate and other chemical mediators for several hours. These chemical mediators contribute to modulation of pruritus and pain. Herein, we investigated the effects of long-term activation of excitatory glutamate receptors on functional expression of transient receptor potential vaniloid type 1 (TRPV1) in dorsal root ganglion (DRG) neurons and then on thermal pain behavior. In order to detect the TRPV1-mediated responses in cultured DRG neurons, we monitored intracellular calcium respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Changes in intracellular calcium were measured with a fluorescent calcium indicator, as described previously (Masuoka et al, 2015 and 2016). For microscopic fluorometric measurement, cultured DRG neurons were washed with ACSF (138.6‐mM NaCl, 3.35‐mM KCl, 21‐mM NaHCO 3 , 9.9‐mM glucose, 0.6‐mM NaH 2 PO 4 , 2.5‐mM CaCl 2 , and 1‐mM MgCl 2 ) and incubated for 45 min in the CO 2 incubator (37 ± 2°C) in a solution containing 3‐μM Fura‐2‐acetoxymethyl ester (Fura‐2 AM; Dojindo Laboratories, Kumamoto, Japan) and 0.005% Cremophor® EL (Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in intracellular calcium were measured with a fluorescent calcium indicator, as described previously (Masuoka et al, 2015 and 2016). For microscopic fluorometric measurement, cultured DRG neurons were washed with ACSF (138.6‐mM NaCl, 3.35‐mM KCl, 21‐mM NaHCO 3 , 9.9‐mM glucose, 0.6‐mM NaH 2 PO 4 , 2.5‐mM CaCl 2 , and 1‐mM MgCl 2 ) and incubated for 45 min in the CO 2 incubator (37 ± 2°C) in a solution containing 3‐μM Fura‐2‐acetoxymethyl ester (Fura‐2 AM; Dojindo Laboratories, Kumamoto, Japan) and 0.005% Cremophor® EL (Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were prepared as described previously (Masuoka et al, 2015(Masuoka et al, , 2016(Masuoka et al, and 2017. Six-to 14-day-old mice were anaesthetized with isoflurane.…”
Section: Preparation Of Primary Drg Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture preparation was conducted as previously described (Masuoka et al, 2015 , 2016 ). The C57BL/6J male and female mice (6- to 14-day-old) were anesthetized by the inhalation of isoflurane (Escain®; Mylan Inc., Cecil Township, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…19,20 Previous studies have found that damaged peripheral tissue can release glutamate 21,22 and activate primary afferent neurons that express mGluR5, causing hyperalgesia. 23,24 The use of selective inhibitors of mGluR5 can significantly reduce hyperalgesia. 25,26 In addition, the process of hyperalgesia induced by mGluR5 may be achieved through PKCε.…”
Section: Introductionmentioning
confidence: 99%